Information Systems Design and Intelligent Applications Proceedings of Fourth International Conference INDIA 2017 (Singapore : Springer Singapore, 2018)
The book is a collection of high-quality peer-reviewed research papers presented at International Conference on Information System Design and Intelligent Applications (INDIA 2017) held at Duy Tan University, Da Nang, Vietnam during 15-17 June 2017. The book covers a wide range of topics of computer science and information technology discipline ranging from image processing, database application, data mining, grid and cloud computing, bioinformatics and many others. The various intelligent tools like swarm intelligence, artificial intelligence, evolutionary algorithms, bio-inspired algorithms have been well applied in different domains for solving various challenging problems.
Preface -- Conference Organizing Committee -- About the Editors -- 108 papers -- Author Index.
Engineering
text file PDF
Keywords: Computational intelligence; Signal processing; Image processing; Speech processing systems; Artificial intelligence